ANALISIS KEKUATAN DOUBLING PLATE JIB CRANE DENGAN FINITE ELEMENT METHOD - Mohammad Rafi, (2023)
In operation the longer the crane is used, corrosion will occur which causes a decrease in the thickness of the metal plate and loss of mechanical integrity and structural failure or damage to metal components. One of the solutions to improve the coating thickness of metal is by adding double plates to the metal that is experiencing the thickness of iron depletion. The addition of double plates serves as an easier and more economical repair of the ship's structure. Jib crane modeling is carried out using Ansys Geometry software, where the basis for its manufacture comes from crane data and materials that have been obtained previously. The results of the jib crane modeling simulation using Ansys Structural are to provide data regarding deformation values and stress values on the modified jib crane placement variation of the addition of double plates to find out how much influence the addition of double plates has on the crane. The results obtained by adding double plates according to their location can significantly reduce deformation and stress on a jib crane with the right location. The addition of double plates with the best placement of double plates from several models that have been tried is by adding double plates on the outer side of the beam.